Pengembangan Bahan Ajar Fisika Berbasis Experiential Learningi terintegrasi Karakter Pada Materi Gerak Harmonik Sederhana Untuk Siswa Kelas X MA - Nopita Pitri; Arini Rosa Sinensis; Siti Anisatur Rofiqah (Pendidikan Fisika Universitas Nurul Huda, 2022)
This study aims to: 1) describe the characteristics of the physics module on the topic of simple harmonic motion based on character-integrated experiential learning; 2) test the feasibility of the module; 3) test the effectiveness of the module. The method used in this research is Research and Development (R&D). The research procedure was in accordance with the research steps described by Borg & Gall. The results of the feasibility test from the expert showed a score of 95% with a very good category from expert lecturer 1, expert lecturer 2 gave a score of 93% in the very good category, and the physics teacher gave a score of 96% in the very good category. Initial trials were carried out to test the initial effectiveness of 3 students with 89.92% results in the very good category. The results of the wide-scale test showed that this module is effective to be used as teaching material with a result of 91.08%. This research produced a product in the form of a physics module based on integrated experimental learning characteristics on simple harmonic motion material for class X MA students